Sekolah Ramah Anak dalam Perspektif Pendidikan Agama Islam pada Jenjang Pendidikan Dasar - Candrasari, Indah; Humaidi, M. Nurul; Arifin, Syamsul (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2022)
Child Friendly Schools are a place to realize the goals of Islamic Religious Education which upholds human dignity, especially in the process of education and child care. The right and correct education and upbringing of students will determine the quality of human beings who are intellectually intelligent and have noble attitudes and behavior. The purpose of this study was to determine the concept of Child Friendly Schools at the basic education level according to the Child Protection Law Number 14 of 2014 and its relevance to Islamic education. This study uses a qualitative approach with a literature review method. Data collection techniques using documentation: editing, organizing, and finding. The results of this study indicate that Child Friendly Schools are the embodiment of a harmonious, safe, and friendly education model based on the principles of non-discrimination, the best interests of children, respecting children's views, and good management of all child-friendly education programs. Child-friendly education has a strong relevance and connection with Islamic education because Islamic education is also a systematic effort carried out in order to develop the potential of students through the provision of educational services that are humanist, inclusive, and uphold the dignity of children. Therefore, Islamic education sees child-friendly education as an inseparable part of the concept of education both ontologically and epistemologically